USA Criminal and Civil Prosecutions Associated with Illicit Online Pharmacies: Legal Analysis and Global Implications. Issue 1 (2017) - Guerra, Camille; Mackey, Timothy K.
The rise of digital technologies has created a complex online environment that now includes illicit Internet pharmacies, online facilitators, advertising sites, and foreign entities. Collectively, these networks create significant patient safety risks, including acting as unregulated access points encouraging prescription drug abuse. Although law enforcement is active in combating this form of cybercrime, there are several difficulties in prosecuting individuals involved in online prescription drug distribution. We characterize these challenges by conducting a comprehensive legal review and analysis of USA civil and criminal cases associated with online pharmacies. This is accomplished by reviewing legal documents/filings available via the Public Access to Court Electronic Records (PACER) database, the Drug Enforcement Agency's website, and structured search queries using the Google search engine. We found more than 100 cases, including criminal indictments, sentencing documents, judgments, forfeiture orders, motions, civil complaints, and restitution documents. Our review indicates that current legal tools and regulatory policies do not effectively deter this highly profitable criminal activity. Hence, we issue a "Call to Action, " advocating the need for more robust legal remedies and criminal penalties, and greater legal and policy coherence at the domestic, regional, and global level aimed at improving patient safety and ensuring the integrity of the drug supply chain.